The last promise - Evans, Richard Paul (Dutton, 2002)
Having followed her new husband to his native home in rustic Tuscany, Ellana distracts herself from her marital disappointments by caring for her asthmatic son, and reevaluates her life when she meets American art lover Ross Story.